Physicochemical properties of wild Rubus fruits with nutraceutical and nutritional potential - Rubio Ochoa, Eréndira; Pérez Sánchez, Rosa Elena; Ávila Val, Teresa C.; Gómez Leyva, Juan Florencio; García Saucedo, Pedro Antonio (Revista Mexicana de Ciencias Agrícolas, 2019)
Rubus species are commonly exploited for fresh consumption, regional gastronomy and traditional herbalism, these benefits are attributed to the presence and action of their polyphenolic metabolites such as flavonoids and anthocyanins, which are known for their antidiabetic, anticancer, etc. In Mexico, around 15 wild species of Rubus are reported. However, population growth has invaded its territory, compromising its growth and development. Therefore, in order to rescue, study and incorporate Mexican wild materials into genetic improvement programs, the objective of this work was to evaluate the physicochemical composition and antioxidant activity in fruits of three wild species (Rubus adenotrichus, Rubus pringlei and Rubus glaucus Beth), compared against a commercial variety (Tupy). To accomplish this, fruits were collected in the state of Michoacán. Physicochemical parameters were evaluated and polyphenols, flavonoids, anthocyanins and antioxidant capacity (CA) were quantified in ethanolic extracts. In the results, the length of the fruit varied from 1.7-2.23 cm and the unit weight of 1.1-3.1 g, the ratio of total soluble solids and titratable acidity of 8.32-14.76. The total polyphenols reported data of 285.06-592.61 mg EAG/100 g PF, total flavonoids of 93.13-36.4 mg EQ/100 g PF and anthocyanins of 18.43-4.32 mg L-1. The CPA of 65.70-25.15 μM ET/g PF. This study showed that wild species comply with physicochemical and nutraceutical characteristics appreciated to be incorporated in breeding programs or the pharmaceutical industry.
Keywords: antioxidant capacity; flavonoids; polyphenols